Spatial accessibility of primary care services among rural population in Selangor, Malaysia - Ab Hamid, Jabrullah (2022)
Disparities of access to health services in rural areas is a global health issue, especially in middle-income countries. Lack of access or delay in getting adequate treatment leads to poorer health outcomes. Recent method called enhanced two-step floating catchment area (E2SFCA) exhibits promising results in quantifying spatial accessibility. Comprehensive understanding of current extent of disparities of accessibility to primary healthcare in local context is essential. This study is to determine the spatial accessibility score to primary care services (clinics) across rural population in Selangor and its associated ecological factors, as well as to propose solutions for primary care service capacity upgrade. This cross-sectional ecological study employed a geographical information system (GIS) based approach to calculate the spatial accessibility, adapted from E2SFCA method considering both public and private clinics. Public clinic refers to health clinics (Klinik Kesihatan) and 1Malaysia mobile clinics govern by the MOH that operated by at least one doctor. Private clinic refers to general practitioner (GP) or private medical clinic. Other types of clinics, dental clinic or primary care services that are provided at hospital is not included for the calculation of spatial accessibility score. Population data was from Housing and Population Census 2010. The spatial pattern of the E2SFCA scores was based on geostatistical tests (Global Moran’s I and Getis-Ord Gi*) and the degree of equality was based on Gini index. Associated ecological factors determined using multiple linear regression. The location-allocation modelling performed to identify optimal locations for public clinic service capacity upgrade, to improve accessibility in low E2SFCA scores areas. High E2SFCA scores areas mainly concentrated surrounding the urban agglomeration at the centre of Selangor, largely contributed by the private sector. Low E2SFCA scores areas predominantly at the northern and coastal regions. Distribution of E2SFCA scores were equal but lower degree of equality observed at the northern region. Rural areas, closer to urban area, higher road density and higher proportion of vulnerable population were positively associated with higher E2SFCA scores (p<0.05). In the location-allocation modelling, coastal areas were prioritised for service capacity upgrade in order to optimise the increment of E2SFCA scores. The level and distribution of E2SFCA scores reflect the performance of primary healthcare. This study provide insight for identifying disparities and areas that need attention as well as potential solutions to resolve the issue. Identification of the influencing factors elucidates the characteristics of the accessibility pertinent to local context. This approach of utilising existing data combined with GIS-based technology delivers great contribution for evidence-based in formulating policy and healthcare planning related to accessibility and resource distribution, such as projecting the health workforce distribution according to the population need. In addition, using existing data routinely collected by the government ease replication for continuous monitoring, as well as can be applied in other health care services.